Techno-economic analysis of oxy-combustion coal-fired power plant with cryogenic oxygen storage - Hanak, Dawid P.; Manovic, Vasilije (Elsevier, 2017)
Around 43% of the cumulative CO2 emissions from the power sector between 2012 and 2050 could be mitigated through implementation of carbon capture and storage, and utilisation of renewable energy sources. Energy storage technologies can increase the efficiency of energy utilisation and thus should be widely deployed along with low-emission technologies. This study evaluates the techno-economic performance of cryogenic O2 storage implemented in an oxy-combustion coal-fired power plant as a means of energy storage. Such system was found to have high energy density and specific energy that compare favourably with other energy storage technologies. The average daily efficiency penalty of the analysed system was 12.3–12.5%HHV points, which is higher than the value for the oxy-combustion coal-fired power plant without energy storage (11.2%HHV points). Yet, investment associated with cryogenic O2 storage has marginal effect on the specific capital cost, and thus the levelised cost of electricity and cost of CO2 avoided. Therefore, the benefits of energy storage can be incorporated into oxy-combustion coal-fired power plants at marginal capital investment. Importantly, implementation of cryogenic O2 storage was found to increase the daily profit by 3.8–4.1%. Such performance would result in higher daily profit from oxy-combustion compared to an air-combustion system if the carbon tax is higher than 29.1–29.2 €/tCO2. Finally, utilisation of renewable energy sources for cryogenic O2 production can reduce the daily efficiency penalty by 4.7%HHV points and increase the daily profit by 11.6%. For this reason, a synergy between fossil fuel electricity generation and renewable energy sources via CO2 capture integrated with energy storage needs to be commercially established.
Keywords: Oxy-combustion; Coal-fired power plant; Energy storage; Cryogenic oxygen storage; Process modelling; Process simulation; Techno-economic analysis